Implementasi Hybrid Contract Pada Perbankan Syariah di Indonesia (Perspektif Fiqih) - Mukhtar Adinugroho; Zujajatul Ílmi; Reizano Amri Rasyid (Jurnal Ilmiah Ekonomi Islam, 2025)
Hybrid Contract is part of the form of ijtihad which is built in order to develop functions and products in Shari'ah Banking, so that Shari'ah Banking can fulfill the needs of the current economic transactions of modern Muslim communities, so that there is a need for innovation in contract development shari'ah. The purpose of this paper is to find out the types of transactions that use Hybrid Contract especially in the Syari'ah Banking area, and analyzed from the standpoint of Islamic economic law (fiqh mu'amalah). The method used is a normative juridical method using data from primary and secondary legal sources, so that there is a match or difference in the theory and facts of economic transactions in Islamic Banking in Indonesia. The results of this study are that the permissibility of multi-contracts based on the principle of the original law of the contract is permissible and the law of multi-contracts is likened to the law of the contracts that build it, must pay attention to the religious provisions that limit it. This means that even though multi-contracts are permitted, there are limits that must not be violated, because these limits are signs for multi-contracts so that they do not fall into prohibited muamalah practices. The limits as explained in the previous section are the boundary lines for multi-contract practices that must not be crossed.